Hybrid Theory of Scattering of Positrons from Helium Atoms - Bhatia, Anand K. (Journal of Atomic, Molecular, Condensed Matter and Nano Physics, 2024)
Hybrid theory of \(L\)-wave scattering of positrons from helium atoms is developed. Phase shifts are calculated for the incident positron momentum from \(0.1\) to \(1.2\) for \(L=0, 1, 2, 3\) before the onset of excitation, and positronium formation. The phase shifts are compared with phase shifts obtained by Drachman, and by Campeanu and Humberston.